2013 Curriculum: The Challenges Based on Vocational English Teachers’ Perspectives - Yudi Basuki; Yeni Nurmala Hidayati (English Teaching Journal : A Journal of English Literature, Language and Education, 2020)
This study aimed at describing and identifying the challenges faced by vocational English teachers in implementing the 2013 curriculum. This study used qualitative research approach conducted in four vocational high schools in Trenggalek and Kediri town, East Java, Indonesia. The data were collected by conducting interview and questionnaire. The results of this study was a number of challenges faced by English teachers dealt with designing the lesson plan, preparing and implementing the materials, learning assessment and classroom management. These challenges, therefore, need more attentions and solutions to succeed teaching and learning process and give better impacts for the English teachers in the implementation of the 2013 curriculum.